Proactive personality and career success. - Seibert, Scott E.; Crant, J. Michael; Kraimer, Maria L. (Journal of Applied Psychology, 1999)
This study examined the relationship between proactive personality and career success by surveying a sample of 496 employees (320 men and 176 women) from a diverse set of occupations and organizations. Proactive personality was positively associated with both self-reported objective (salary and promotions) and subjective (career satisfaction) indicators of career success. Hierarchical regression analyses showed that proactive personality explained additional variance in both objective and subjective career success even after controlling for several relevant variables (demographic, human capital, motivational, organizational, and industry) that have previously been found to be predictive of career outcomes. These findings were consistent using both self-report and significant–other ratings of proactive personality.